An examination of the humidity correction by Vaisala RS80-A radiosondes for experiments and measurements at an inland Antarctic station - Hirasawa, Naohiko; Hayashi, Masahiko; Yamanouchi, Takashi (National Institute of Polar Research, 2003)
P(論文) The present paper examines the correction of humidity measurements by the Vaisala RS80-A radiosonde using data obtained at Dome Fuji Station, inland Antarctica. The correction method is based upon a procedure developed by L.M. Miloshevich et al.(J. Atmos. Oceanic Technol., 18, 135, 2001). In the present study, experiments in a snow cave below ground, where a state of ice saturation is assumed, show that Miloshevich's coefficient is appropriate for temperatures warmer than -45 °C because the corrected humidity reflects the state of ice saturation. Below these temperatures a correction coefficient is needed. At -55 °C , for example, a factor of 1.2 is needed. An examination using surface humidity data obtained from a routine aerological observation concluded that the correction coefficient is larger than Miloshevich's at temperatures colder than -50 °C , so that the multiplication factor(0.185968×exp((-0.0339)×T); T=temperature) is needed to apply Miloshevich's coefficient. After the correction is performed, the relative humidity with respect to ice becomes 150 on average in the lower temperature range. Perpetual falling of ice crystals indicates at least an occurrence of ice saturation; this condition of high relative humidity is supported by downwelling of a large amount of water vapor in an intense temperature inversion layer and an extremely small number of ice nuclei, suggested by in-situ data. An improved correction applied to a vertical profile in the temperature inversion layer reveals that supersaturation with respect to ice appears at all levels. In the lowest layer, humidity increases with decreasing height, although observed data show steep dryness with decreasing height. This is considered a measurement error. departmental bulletin paper